Assessment of potential bioavailability of heavy metals in the sediments of land-freshwater interfaces by diffusive gradients in thin films. (January 2018) - Song, Zhixin; Dong, Lixin; Shan, Baoqing; Tang, Wenzhong
Abstract: It is important to understand the potential bioavailability of heavy metals in the sediments of land-freshwater interfaces (between terrestrial and aquatic ecosystems). Therefore, we evaluated the pollution of Cr, Ni, Cu, Zn, As, and Cd in land-freshwater interface sediments/soils according to total concentrations, and used sequential extraction method to measure different fractions of Cd. Then, the diffusive gradients in thin films (DGT) technique was employed to study the potential bioavailability of metals. Results showed that the concentrations of exchangeable and weak acid soluble fraction and oxidizable fraction were higher in ecotone area, and the values of reducible fraction and residual fraction were higher in deep water area. There existed significant positive correlations between [Cd]-DGT (concentration of Cd measured by DGT) and EXC-Cd (exchangeable and weak acid soluble fraction of Cd) (r 2 = 0.65), but the significant negative correlation was found between [Cd]-DGT and RES-Cd (Residual fraction of Cd) (r 2 = 0.52). DGT technique is a feasible method to measure potential bioavailability of heavy metals for risk assessment in the sediments/soils of land-freshwater interfaces. Graphical abstract: Image 1 Highlights: DGT was used for assessment potential bioavailability of heavy metals in sediments. Cd distribute characteristics of land-freshwater interface sediments were investigated. Ecotone area was more prone to show ecological risk associated with metals. Pollution assessment based on total concentrations was affected by background values.